Proceedings. Frontiers in Education. 36th Annual Conference 2006
DOI: 10.1109/fie.2006.322749
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Teaching an Integrated Series of Courses in Embedded Computer Systems

Abstract: With embedded computer systems being a core topic in computer engineering, there are typically one or more courses in a program that provide varying coverage. Many universities offer introductory courses that focus on microcontroller-based systems and embedded programming. Advanced courses often do not have a common focus and are not available until the graduate level, leaving a gap in training undergraduates. At Iowa State University, the Department of Electrical and Computer Engineering developed a new senio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Some universities [17,18,19,20] offered this course as a senior-level undergraduate course as they observed that students at senior level have already been exposed to microcontroller software and hardware design, but the combination of the two is rarely touched. Among them, Iowa State [18,19], provide an introductory course in system level design at undergraduate level as well as an advanced course in graduate level to address competing new technologies. The advantage of this approach is the undergraduate level course allows the students to focus on a more general view of system-level design and gain systemlevel design experience without spending the time to learn a system-level design language, which will be stressed in the graduate level course.…”
Section: Level Of the Course: Undergraduate Ormentioning
confidence: 98%
“…Some universities [17,18,19,20] offered this course as a senior-level undergraduate course as they observed that students at senior level have already been exposed to microcontroller software and hardware design, but the combination of the two is rarely touched. Among them, Iowa State [18,19], provide an introductory course in system level design at undergraduate level as well as an advanced course in graduate level to address competing new technologies. The advantage of this approach is the undergraduate level course allows the students to focus on a more general view of system-level design and gain systemlevel design experience without spending the time to learn a system-level design language, which will be stressed in the graduate level course.…”
Section: Level Of the Course: Undergraduate Ormentioning
confidence: 98%
“…According to the National Academies, one of two major tasks required to generate desired student learning outcomes is "better alignment of engineering curricula and the nature of academic experiences with the challenges and opportunities graduates will face in the workplace" 11 . In fact, the same report states that "the disconnect between the system of engineering education and the practice of engineering appears to be accelerating" 10 . The volume of information that engineers are collectively called upon to know is increasing far more rapidly than the ability of engineering curricula to "cover it."…”
Section: Introductionmentioning
confidence: 99%
“…Further, engineering curricula usually present the set of topics engineers "need to know," leading to the feeling that an engineering education is simply a collection of courses. While the content of the courses may be valuable, this view of engineering education ignores the need for connections and integration 10 . According to the National Academies, one of two major tasks required to generate desired student learning outcomes is "better alignment of engineering curricula and the nature of academic experiences with the challenges and opportunities graduates will face in the workplace" 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Bezdek et al [2] describe a more narrowly focused effort for a three-course sequence related to embedded systems, with the key issue being the introduction of the middle course as a new course relative to the first and last in the sequence. This sequence is later in the curriculum, ostensibly after introductory courses on digital logic and computer organization, and includes a graduate-level embedded-systems course as the final element in the se-University of Toronto; June 4 -7, 2017 -2 of 6 -quence.…”
Section: Samples Of Related Workmentioning
confidence: 99%